Hypotension and digestive anastomotic leakeage. An experimental study. - Esperón, Alejandro; Percovich, Carlos; Estrada, Daniel; Lussheimer, Daniel; Aprikián, Darío; Salom, Andrés; Bonaba, Roberto (Cirugía del Uruguay, 1987)
The authors analyse the importance of hypotension due to acute hypovolemia as an etiopathological factor in digestiva suture leakage. AMstomoses at dlfferent intestinal levels were made in dogs submitted to extreme hypotension due to per and immediate post-operative haemorrhage. The authors come to the conclusion that hypotension as an isolated factor does no play an essential role in the appearance of digestive suture leakage in dogs.